Pengujian Association Clasification Dalam Meningkatkan Kualitas Minyak Sawit Sebagai Bahan Dasar Biodisel - Adi Fitra Andikos; Helly Andri (STMIK Budi Darma, 2019)
The role of oil and gas business in Indonesia has always influenced the source of revenue from the country and energy sources for the national economy. In the 1970 's to the 1990 's and mid-1990 's, it was characterized by the high dependence of the national economy on oil and gas revenues, triggering massive oil and gas-producing. Currently, Indonesia is the largest palm oil producer and exporter in the world. Palm oil is one of the roads to overcome the problem of petroleum in Indonesia. To commercialize plants is still constrained because the availability of low raw material costs very hard to get. The amalgamation of crude palm oil and crude palm sludge is one of the problems of raw materials for renewable energy production. This low-level oil has great potential as a raw material for biodiesel production. To get the maximum quality mixing required a computer method. The method used in this study is analysis study with the Association classification approach by testing Improved Apriori algorithm in mining palm oil dataset. In this research using Data Mining application so that can be used to display the information of quality improvement of palm oil acid with high quality as a biodiesel base where the information is seen from the value of support and Confidence between items. M-Apriori algorithm can not read the continous data, so it must be done transformation first, one of them using the help of discreetization technique. Crude palm oil acid type esteridication which is fatty acid levels > 60 and Abu bunches 51-100 g/mol then the quality of biodiesel with the result of rising methyl Ester increases by as much as 100% (confidence: 1). From data that is calculated manually, no relationship is found Association.